ISOLASI DAN IDENTIFIKASI JAMUR Colletotrichum spp. ISOLAT PCS PENYEBAB PENYAKIT ANTRAKNOSA PADA BUAH CABAI BESAR (Capsicum annuum L.) DI BALI - Sudirga, Sang Ketut (Metamorfosa: Journal of Biological Sciences; Vol 3 No 1 (2016)DO - 10.24843/metamorfosa.2016.v03.i01.p04, 2016)
A research on the isolation and identification of fungi Colletotrichum spp. PCS isolate as the cause of anthracnose desease on chili fruit ( Capsicum annuum L.) in Bali. Fungi Colletotrichum spp. isolated from large chilies anthracnose symptoms were taken from three locations of chili planting in Bali i.e. Apuan Village, Tabanan (isolates APN), Village Belok Sidan, Badung (isolates BLS) and Village Pancasari, Buleleng (isolates PCS). To ensure that these three isolates of the fungus caused anthracnose on chili fruit, tested Koch's postulates and virulence test were used. Based on fungal virulence test, isolates PCS was the most virulent isolates than APN and BLS isolates, therefore the PCS isolates was further identified. Macroscopic  and microscopic identification of the fungus Colletotrichum spp. isolate PCS were conducted at the Laboratory of Biopesticides, Faculty of Agriculture, University of Udayana by observing the shape of the colony, colony color, growth rate, hyphae structure, spore shape, and size of the spores. The identification of the fungus Colletotrichum spp. isolate PCS was carried out in the Department of Molecular Biology, Faculty of Mathematics and Natural Sciences, Bogor Agricultural University based on the analysis of 18S rRNA genes by using ITS1 and ITS4 primers. Phylogeny analyzes were performed using the MEGA 6.0, maximum parsimony method (MP) with 1000x bootstrap. The results showed that the fungus Colletotrichum spp. isolate PCS was a fungal of Colletotrichum acutatum as a clade with sequences of fungus C. acutatum by 100% of Bootstrap Support (BS).
Keywords: isolation, identification, isolate, phylogeny, clades